Engineered carbon nanomaterials by light-matter interaction - Chen, Pingping (Kansas State University, 2023)
Synthesis of unique nanomaterials and advancement of their transformative properties play key roles to meet the application in future nanoelectronics, nanophotonics, plasmonics, and reconfigurable electronics. Graphene, the first two-dimensional and atomically thin film arranged in hexagonal honeycomb lattice of carbon atoms, exhibits excellent electronic, photonic, mechanical, and thermal properties, and was early predicted to be an excellent candidate to replace traditional semiconductor, i.e., silicon. However, with the realization of its zero-energy bandgap, it spurred further research to open a band gap in graphene. The fabrication of graphene nanoribbons with narrow physical width of ribbons appeared to be a promising approach to achieve the above goal. However, fabricating ultrathin (sub-20 nanometer) graphene nanoribbons (GNRs) is extremely challenging even with the help of a state-of-the art electron beam lithography facility. In contrast, the growth and development of ultranarrow carbon nanotubes (CNTs) (diameter ~ few nanometers to 1.5 nm) are an established technology that may suitably be leveraged to innovate the synthesis of GNRs, and possibly new carbon nanomaterials. The research in this dissertation work seeks to study CNT characteristics and provides an approach to create and fundamentally understand GNR synthesis. By employing an ultrafast laser irradiation to CNTs to alter the shape and transform the metallic electronic phase of CNTs to semiconducting/semi-insulating phases of GNRs and hybrid GNR/nanocrystals, an important milestone for future electronics and photonics is demonstrated. An ultrafast laser-based approach is developed to explore experimental light-matter interaction conditions to fabricate GNRs from multi-walled carbon nanotubes (MWCNTs). By using a high-intensity electromagnetic field to interact with the CNTs, this study successfully demonstrates the nanomachining of carbon nanotubes and their transformation to graphene nanoribbons and carbon nanocrystal hybrids. The ribbons are narrow (typically, less than 15 or 20 nm in width but could be further scaled down by choosing tubes of smaller diameters), while the nanocrystals showing well-defined crystalline structures are embedded along the length of the ribbons with ~ 15 nm to down to ~ 3 nm in size. It is found that the transformation from the MWCNTs to GNRs is more sensitive to the overall laser intensity and less sensitive to laser spot sizes and radiation time. To understand the transformation from MWCNTs to GNRs, a thermal response of MWCNTs under exposure to intense femtosecond pulses is investigated, by developing a heat-transfer Multiphysics model based on the finite element analysis method. Further experiments are achieved in this work to obtain sub-10 nanometer ribbons that are promising for future applications. One big challenge to exploit the extraordinary properties of GNRs in nanophotonics and nanoelectronics is to fabricate aligned GNR arrays. Compared to a single GNR, GNR arrays have higher response signal intensity (current or light intensity) and hence better performance. This work proposes a mechanism to fabricate aligned GNR arrays by first aligning CNTs. By combining an inkjet printing technique and the dielectrophoretic technique a proof-of-concept of fabrication of CNT arrays are demonstrated. Furthermore, the inkjet printing method is a fast, controllable, and low-cost method. Electrodes are designed and printed for dielectrophoretic (DEP) to achieve individual carbon nanotube alignment. This DEP alignment approach also has the advantage of eliminating chemicals from the patterned structures and the flexibility in adoption, compared to other expensive methods that involve lithographic processes. The concluding part of the study is to investigate the optical responses, specifically the plasmonic properties of individual and aligned GNRs, especially aiming to manipulate the optical responses of GNRs to the near-infrared wavelength range. A Multiphysics model is developed to study the plasmonic properties of the individual and GNR arrays based on the finite element analysis method. It is found that when the width of GNR becomes smaller, the surface plasmon resonant wavelength can be tuned from the mid-infrared (9 µm) to the near-infrared (2.5 µm) range. Further research can be pursued, including experimental fabrication and demonstration of these devices, by doping the GNRs to increase the Fermi energy of the electrons and thereby tuning the resonant wavelength to the visible light range.
Keywords: Graphene nanoribbons; Nanoelectronics; Nanophotonics; Plasmonics; Ultrafast laser